Effect of NO2 sequestered recycled concrete aggregate (NRCA) on mechanical and durability performance of concrete. (November 2020) - Ariyachandra, Erandi; Peethamparan, Sulapha; Patel, Shrish; Orlov, Alexander
Abstract: The utilization of recycled concrete as an adsorbent to sequester NO2 without additives or catalysts is an innovative, cost-effective, and sustainable approach to capture NO2 from targeted industrial facilities. This paper presents the mechanical and durability performance of ordinary portland cement (OPC) concrete containing NO2 sequestered recycled concrete aggregate (NRCA). NRCA was used as a partial replacement for natural fine aggregate at 20% and 40% rates by volume. The incorporation of NRCA in concrete resulted in increased compressive strength, decreased water-permeable porosity, and reduced chloride ion migration. Moreover, test mixtures comprising 40% NRCA showed a significant chloride binding capacity compared to control concrete mixtures. Furthermore, high replacement rates of NRCA noticeably enhanced the resistance to chloride-induced corrosion of steel in concrete or at least was on par with the performance of a commercially available calcium nitrite-based corrosion inhibitor.